(untitled) (Revista Apotheke, 2024)
The aesthetic theory developed by John Dewey and presented in his 1934 book, “Art as Experience”, is considerably influenced by modern art and artists. This influence, however, has so far received little attention from interpreters. The aim of this article is precisely to shed light on these relationships by presenting the relationship between the philosopher and the French painter Henri Matisse. The hypothesis is that these encounters between artist and thinker had an impact on Dewey’s philosophy of art. The argument is divided into four parts. In the first, the context in which the meetings took place was discussed, namely the Barnes Foundation. This was followed by a review of the historical letters from these meetings. Thirdly, we sought to understand the theoretical impact of this exchange on Dewey’s aesthetics.Finally, brief concluding remarks were presented.